Industrial Engineering and development. - Carrión Muñoz, Rolando Víctor (2008)
In the mission, approved by consensus, refers that the investigation in the faculty contributes to the “sustainable development of the society”. And according to the industrial engineering professional background of San Marcos University, graduates develop many actions, among others, for the “human development”. This article demonstrates that the human and sustainable development are expressions that have substituted the term “development”, that has been losing its original meaning, as it has been related only to its economic sense.